Syntagma as a Unit of the Speech Experience Analysis - Orap, Maryna (East European Journal of Psycholinguistics, 2015)
The article deals with the problem of the analysis of speech experience’s unit. The investigation of speech experience enabled to analysis the elements and identify internal and external structures and patterns of its organization. Further investigation of the speech experience’s content is impossible without the analysis of its units. In the result of the theoretical analysis we defined syntagme as a unit of the speech experience. Definition syntagma as a unit of speech, in which, as in the smallest particle implemented in the unity semantic, syntactic and intonational aspects, makes it possible to analysis syntagme as a unit, which reflects the general features of speech experience. To approof the hypothesis, we performed an analysis of narratives in two age samples for the purpose to catch out the dominant type of syntagma. The results of empirical studies have demonstrated that the development and improvement of speech experience is in the direction of increasing the proportion of relational and object syntagmatic in the texts. This means that improving the ways and means of individual speech mastering of the world is reflected in the increase and expansion of relations in which meaning of the word is involved in the structure of speech experience. Thus, taking into account certain patterns of speech experience, we concluded that the syntagm as a unit of speech experience allows to describe features of the structure and content of all structural elements of speech experience.ReferencesChepelieva, N. (2009). Rozuminnia ta interpretaciia osobystogo dosvidu u kontekstipsykhologichnoi germenevtyky [Understanding and interpretation of personal experience in thecontext of psychological hermeneutics]. Naukovi Zapysky Natsionalnogo Universytetu “OstrozkaAkademia”, 12, 8–21. Retrieved from: http://nbuv.gov.ua/j-pdf/Nznuoapp_2009_12_4.pdfFilatova, O. (2012). Movni I movlennevi odynyci ta yih vidnoshennia do porodzhennia,structuruvannia I spryimannia movlennia [Language and speech units and their relation to thegeneration, structuring and perception of the speech]. Lingvistychni Studii, 25, 43–48.Filatova, O. (2010). Sintagma kak edinitsa porozhdeniya i vospriyatiya rechi, eyosmyislovyie i grammaticheskie priznaki [Syntagma as a unit of generation and perception ofspeech, its semantic and the grammatical features]. Aktualni Problemy Slovjanskoji Filolohii, 3,315–324.Orap, M. (2014). Psikholohiya Movlennevogo Dosvidu Osobystosti [The psychology ofthe personality’s speech experience]. Ternopil: Pidruchnyky i Posibnyky.Reformatskiy, A. (2004). Vvedenye v Yazykovedenije [Introduction to Linguistics].Moscow: Aspekt-Press.Setrov, M. (1972). Osnovy funktsionalnoi teorii organizatsii [Basics of the functionaltheory of organization]. Leningrad: Nauka.Vygotsky, L. (2000). Mysl i Slovo [Thought and Word]. (pp. 462–512). In: Psikholohiya.Moscow: PERSEWittgenstein, L. (1995). Filosofski Doslidzhennia [Tractatus Logico-Philosophicus].Kyiv: Osnovy. Retrieved from: http://filosof.historic.ru/books/item/f00/s00/z0000273/